FACTORS INFLUENCING CONSUMERSâ REPURCHASE INTENTION TOWARDS SHOPEE INDONESIAâS STAR SELLER OF HANDPHONE ACCESSORIES - Syafina Dewi, Putri
In Indonesia, the increasing number of consumers who do online shopping is caused by the rising number of internet users. As a result of government limitations limiting people's mobility and COVID-19's spread, consumers are likely to continue shopping online, especially in e-commerce, for reasons other than health, such as convenience, time savings, and product choices. Technology improvements and more people working from home (WFH) since the pandemic hit have led to a rise in the number of people in Indonesia who use the internet. This, in turn, has led to a rise in handphone users. As the number of handphone users in a community grows, so does the growth of supporting industries, namely handphone accessories. The primary purpose of this research was to understand factors influencing consumers' repurchase intention on handphone accessories in Shopee. The author chose this topic since the repurchase intention on handphone accessories has the lowest percentage in the preliminary study. The questionnaire was distributed through an online survey in Greater Jakarta with 210 respondents who had purchased handphone accessories in Shopee. This research uses PLS-SEM to analyze the collected data. The results of this research portray that perceived value and perceived price significantly influence customer satisfaction but did not significantly influence consumers' repurchase intention. Customer satisfaction significantly influences both customer trust and consumers' repurchase intention. Furthermore, customer trust significantly influences consumers' repurchase intention. E-commerce practitioners will benefit from the findings of this research when addressing the significance of customer satisfaction and trust in e-commerce' consumers' repurchase intention.